2004
DOI: 10.1038/labinvest.3700056
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic analysis of gastric MALT lymphoma-like lesions induced by Helicobacter pylori infection in neonatally thymectomized mice

Abstract: Most gastric mucosa-associated lymphoid tissue (MALT) lymphomas are caused by Helicobacter pylori (H. pylori) infection. We previously reported that acquired lymphoid follicles with germinal centers were induced by H. pylori infection in neonatally thymectomized (nTx) mice. In the present study, we developed gastric MALT lymphoma-like lesions in nTx mice by long-term H. pylori infection, and performed immunogenetic analyses. BALB/c mice were thymectomized on the 3rd day after birth. At 6 weeks of age, mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Enno et al reported observing H. felis-associated gastric MALT lymphomas in normal BALB/c mice, and they found lymphoepithelial lesions in 88% of the animals and lymph follicles in 38% of the animals 22 months after infection (6). Fukui and colleagues reported observing H. pylori-associated gastric MALT lymphomas in neonatally thymectomized BALB/c mice, and they found lymph follicles and lymphoepithelial lesions in 60% of the mice in the absence of Bcl-X immunoreactivity (9). In addition, Bcl-X-immunoreactive cells were found in these mice 6 and 12 months later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enno et al reported observing H. felis-associated gastric MALT lymphomas in normal BALB/c mice, and they found lymphoepithelial lesions in 88% of the animals and lymph follicles in 38% of the animals 22 months after infection (6). Fukui and colleagues reported observing H. pylori-associated gastric MALT lymphomas in neonatally thymectomized BALB/c mice, and they found lymph follicles and lymphoepithelial lesions in 60% of the mice in the absence of Bcl-X immunoreactivity (9). In addition, Bcl-X-immunoreactive cells were found in these mice 6 and 12 months later.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, MALT lymphomas have been reported following infection with Helicobacter mustelae in ferrets (7), following infection with Helicobacter felis in normal BALB/c mice (6), following infection with H. pylori in neonatally thymectomized BALB/c mice (9), and following infection with "Candidatus Helicobacter heilmannii" in normal BALB/c mice (19,21). In this study, we used the "Candidatus Helicobacter heilmannii" previously obtained from a cynomolgus monkey to infect C57BL/6 mice for up to 24 months.…”
mentioning
confidence: 99%
“…Sections were stained with hematoxylineosin for histopathology and May-Giemsa for assessment of H. felis colonization. 18 The degree of gastritis was determined using the scoring system as described previously. 19 Chronic inflammation, characterized by infiltration of mononuclear cells, was graded from 0 to 3, where 0 ¼ no increase in the number of inflammatory cells, 1 ¼ slight infiltration of the lamina propria by lymphocytes and plasma cells, 2 ¼ moderately dense infiltration of the lamina propria by lymphocytes and plasma cells, 3 ¼ very dense lymphoplasma-cell infiltration in the lamina propria.…”
Section: Histologic Examinationmentioning
confidence: 99%
“…Indeed, C57/ black mice, a representative Th1-predominant strain, develop severe corpus gastritis, 34 whereas Balb/c mice, a Th2-predominant strain, never develop gastritis although of the mouse strains examined, they have the highest level of H. pylori colonization in their gastric mucosa. 35 Moreover, when we perform neonatal thymectomy in these mice to inhibit the development of CD25-positive inhibitory T cells, the development of gastritis in C57/black mice is greatly reduced, whereas most Balb/c mice develop MALT lymphoma [35][36][37][38] (Fig. 4).…”
Section: Gastritismentioning
confidence: 99%
“…Indeed, among various mouse strains, only Balb/c mice thymectomized 3 days after birth developed MALT lymphoma following H. pylori infection. [35][36][37][38]59 In the gastric mucosa of those mice, in addition to IFN-γ expression, IL4 expression, which has never been observed in H. pylori-induced gastritis, was detected. 35,38 The Balb/c mouse is a typical Th2-predominant strain, and thymectomy enhances the autoimmune reaction by inhibiting the development of CD25 inhibitory CD4 T cells.…”
Section: Mucosa-associated Lymphatic Tissue Lymphomamentioning
confidence: 99%